Analysis of Patients with Major Fractures with and without COVID-19 Infection - Cansabuncu, G; Akalin, Y; Çevik, N; Duran, M; Öztürk, A (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY As in orthopedic trauma patients, a hyperinflammatory response due to cytokine release occurs in patients with moderate and severe COVID-19 infection. In these patients, untimely surgical intervention can create more destructive situations in the postoperative period. Our aim in this study was to investigate the effect of COVID-19, trauma and surgical intervention on acute phase reactants' levels in patients with and without COVID-19 infection. MATERIAL AND METHODS Twenty-four patients diagnosed with COVID-19 infection and major fractures requiring surgical treatment were evaluated retrospectively (Group 1). Twenty-four COVID-19 negative patients with similar trauma were included in the study as a control group (Group 2). These two groups were compared in terms of demographic data, time to surgery, total hospitalization time, and preoperative and postoperative acute phase reactants' [C-reactive protein (CRP), D-dimer, ferritin, fibrinogen and white blood cell (WBC)] values. RESULTS Time to surgery was 8.3 ± 0.7 days and the total hospital stay was 15.2 ± 0.8 days, in Group 1. These values were determined as 3.3 ± 0.4 and 6.5 ± 0.6 days, respectively for the patients in Group 2 (p < 0.001 and p < 0.001, respectively). When the acute phase reactant values studied during admission were examined, a significant difference was found between the two groups in terms of CRP, D-dimer, ferritin and WBC (p = 0009, p = 0.002, p < 0.001 and p < 0.001, respectively). In the preoperative period, a significant difference was observed between the groups in terms of CRP and ferritin (p = 0.011, p < 0.001, respectively). A significant difference was found only in terms of ferritin from the laboratory values studied in the postoperative period (p < 0.001). DISCUSSION To our knowledge, the present study is the first study which compares and investigates the effects of COVID-19 infection, major fracture and surgical intervention on acute phase reactants' values. Surgical treatment is generally recommended as soon as possible in daily orthopedic practice. However, in patients with asymptomatic or mildly symptomatic COVID-19 infection, it remains unclear how long surgical intervention will be delayed after admission and clinical stabilization of patients with a fracture that requires surgical fixation. In a meta-analysis, patients with COVID-19 infection accompanying hip fracture had a mortality rate of 32.6% in the early postoperative period, and the mortality risk of these patients was found to be 5.66 times higher compared to patients without COVID-19 infection. In our study, one patient (4.2%) with COVID-19 infection who underwent partial hip arthroplasty due to femoral neck fracture. CONCLUSIONS The follow-up and treatment of patients with COVID-19 infection with accompanying a major fracture requiring orthopedic surgery is a complex situation. We recommend that acute phase reactants such as CRP, D-dimer, erythrocyte sedimentation rate (ESR), and ferritin should be closely monitored in these patients during the period from admission to surgery, and surgical intervention should be performed while these values are in remission or decline. Key words: COVID-19, fracture, trauma, acute phase reactants, surgical timing.
Keywords: Ferritins; C-reaktivní protein; lidé; retrospektivní studie; Acute-Phase Proteins; Hip Fractures; proteiny akutní fáze; C-Reactive Protein; fraktury kyčle; Retrospective Studies; COVID-19; ferritiny; Humans